The Role of Sharia Banking Lecturer in Motiving Febi Students to Transaction in Sharia Bank - Milda Madani (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
The Palopo State Islamic Institute has a Faculty of Islamic Economics and Business, the Islamic Banking Study Program. Students, especially Islamic banking study programs, should be able to understand the world of Islamic banking so that this can trigger students' interest in using Islamic banks as a transaction tool. The research carried out was using a type of descriptive qualitative research method with a Field Research approach by examining directly the object to be studied. The data and data sources used in this study are primary and secondary data and techniques in data collection were obtained from observation, interviews and documentation. The instruments in this study were cell phones, cameras, and interview guides. Then analyzed further and drawn a conclusion. Based on Soerjono Soekanto's theory and data found from informants, the results of the study show that the lecturer has carried out his role by providing an introduction to Islamic banking courses through the learning process in the classroom and then the campus has also provided facilities to support student motivation towards interest in transactions in Islamic banks. Also, the campus has collaborated with external parties, in this case, namely BSI and Bank Muamalat in providing socialization regarding the products offered. Then the obstacle is the lack of Automated Teller Machines in the area where students live so this is an excuse for students not to use Islamic banks as a transaction tool.